Mengembangkan Branding Dan Desain Yang Menarik Di Era Digital - Dimas Alfian Maulana; Ananda Dwi Saputra; Fionna Dwy Arianti; Veta Lidya Delimah Pasaribu (CV. ITTC INDONESIA, 2025)
Community Service Activities (PKM) serve as a key step and main focus for university students to foster a positive mindset toward society. Focusing on entrepreneurship has become a very relevant topic today, as many MSMEs are able to sell a variety of products but lack branding and promotional strategies that align with the current global trends. In this regard, we as students play a role in conducting socialization about the development of digital marketing and branding that can compete with established brands. We also realize that many MSME actors feel challenged by larger brands, whose prices are often set higher than their market range. The method we used is participatory action research. The findings show that PKM activities have successfully established an organized structure, but there were challenges encountered during the process, such as limited time for conducting the socialization. With sufficient time, PKM activities can be fully achieved. We hope that through branding socialization in this digital era, Indonesian youth will be more interested in entering the business world. The method we used is participatory action research. The findings show that PKM activities have successfully established an organized structure, but there were challenges encountered during the process, such as limited time for conducting the socialization. With sufficient time, PKM activities can be fully achieved. We hope that through branding socialization in this digital era, Indonesian youth will be more interested in entering the business world.